Wheat beta-expansin (EXPB11) genes: Identification of the expressed gene on chromosome 3BS carrying a pollen allergen domain - Jia Jizeng; Zhang Juncheng; Kong Xiuying; Békés Ferenc; Dunn David S; Li Dora; Breen James; Wicker Thomas; Mago Rohit; Ma Wujun; Bellgard Matthew; Appels Rudi (BMC Plant Biology, 2010)
Abstract Background Expansins form a large multi-gene family found in wheat and other cereal genomes that are involved in the expansion of cell walls as a tissue grows. The expansin family can be divided up into two main groups, namely, alpha-expansin (EXPA) and beta-expansin proteins (EXPB), with the EXPB group being of particular interest as group 1-pollen allergens. Results In this study, three beta-expansin genes were identified and characterized from a newly sequenced region of the Triticum aestivum cv. Chinese Spring chromosome 3B physical map at the Sr2 locus (FPC contig ctg11). The analysis of a 357 kb sub-sequence of FPC contig ctg11 identified one beta-expansin genes to be TaEXPB11, originally identified as a cDNA from the wheat cv Wyuna. Through the analysis of intron sequences of the three wheat cv. Chinese Spring genes, we propose that two of these beta-expansin genes are duplications of the TaEXPB11 gene. Comparative sequence analysis with two other wheat cultivars (cv. Westonia and cv. Hope) and a Triticum aestivum var. spelta line validated the identification of the Chinese Spring variant of TaEXPB11. The expression in maternal and grain tissues was confirmed by examining EST databases and carrying out RT-PCR experiments. Detailed examination of the position of TaEXPB11 relative to the locus encoding Sr2 disease resistance ruled out the possibility of this gene directly contributing to the resistance phenotype. Conclusions Through 3-D structural protein comparisons with Zea mays EXPB1, we proposed that variations within the coding sequence of TaEXPB11 in wheats may produce a functional change within features such as domain 1 related to possible involvement in cell wall structure and domain 2 defining the pollen allergen domain and binding to IgE protein. The variation established in this gene suggests it is a clearly identifiable member of a gene family and reflects the dynamic features of the wheat genome as it adapted to a range of different environments and uses. Accession Numbers: ctg11 =FN564426 Survey sequences of TaEXPB11ws and TsEXPB11 are provided request.